Safety and effectiveness of laparoscopic renal biopsy: a single-center review and meta-analysis - Lingling Xu; Xueqin Bian; Jian Yang; Hongying Xu; Yi Fang; Junwei Yang; Lei Jiang; Ping Wen (Renal Failure)
Background While renal biopsy remains the preferred diagnostic method for assessing proteinuria, hematuria, or renal failure, laparoscopic renal biopsy (LRB) can serve as an alternative for high-risk patients when percutaneous kidney biopsy (PKB) is not recommended. This study was aimed to evaluate the safety of LRB.Methods In study 1, Fourteen patients from January 2021 to January 2023 had a LRB taken for various indications, such as morbid obesity, abnormal kidney construction, uncontrolled hypertension, and coagulopathy. We also conducted a Meta-analysis of the success rate and complication rate of previous LRB in study 2.Results All the patients completed biopsies and adequate renal tissues were obtained. The success rate was 100%. The median number of glomeruli obtained was 22.5 (range:12.0, 45.0). The complication rate was 7.1% (urinary tract infection). There were no significant differences between levels of hemoglobin, serum creatinine, and urinary NAGL before and after surgery. In the meta-analysis, the success rate of operation, satisfactory rate of sample, and complication rate of surgery were 99.9%, 99.1%, and 2.6% respectively.Conclusion LRB can achieve a good success rate and specimen retrieval and does not increase the risk of complications for high-risk patients. It can present as one of the alternative methods for patients with glomerular diseases.